2008
DOI: 10.1902/jop.2008.070247
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Surgical Periodontal Therapy With Adjunctive Chlorhexidine Use in Adults With Down Syndrome: A Prospective Case Series

Abstract: Satisfactory healing responses were achieved following non-surgical mechanical periodontal therapy with the adjunctive use of chlorhexidine and monthly recalls in adults with DS with chronic periodontitis and mild-to-moderate learning disabilities. Such a treatment regimen seems appropriate and beneficial for adults with DS and chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
1
20
0
3
Order By: Relevance
“…Dental abnormalities are usually observed, including abnormal structure, number, eruption and position of teeth, as well as a high incidence of dental caries (4) and periodontal disease (5). Adults with DS might be more prone to suffering falls due to impaired motor development (6).…”
Section: Introductionmentioning
confidence: 99%
“…Dental abnormalities are usually observed, including abnormal structure, number, eruption and position of teeth, as well as a high incidence of dental caries (4) and periodontal disease (5). Adults with DS might be more prone to suffering falls due to impaired motor development (6).…”
Section: Introductionmentioning
confidence: 99%
“…After non-surgical periodontal treatment, oral niches in favor of periodontal bacteria can shift from a predominantly Gram-negative to a Grampositive subgingival microbiota. However, currently very little data are available in the literature on the microbiological outcome after non-surgical periodontal therapy in the Chinese population (Xu et al, 2004;Cheng et al, 2008). Moreover, while previous studies assessing the microbiological effects of periodontal therapy mainly used the techniques of culture, DNA probe or polymerase chain reaction (PCR), recent oral research has used quantitative real-time PCR (qRT-PCR), due to its accurate and rapid assessment of microbiological levels (Gomes et al, 2008;Cionca et al, 2010).…”
mentioning
confidence: 99%
“…The authors compared individuals who had frequent dental visit (mean intervals between visits: 3.7 ± 1.3 months) versus those who had visits more than one year apart and revealed that the regular review group had better clinical parameters. Cheng et al (2008) reported satisfactory healing response on 21 DS individuals treated by non-surgical mechanical periodontal therapy (followed by monthly recalls) and the adjunctive use of chlorhexidine gel for toothbrushing and chlorhexidine mouthwash twice daily. It appears from the above conflicting and varied findings, conventional periodontal therapy which involves oral hygiene instructions, scaling and root debridement cannot guarantee good gingival healing response.…”
Section: Periodontitismentioning
confidence: 99%